The Influence of Audio-Visual Advertising Media on the Ability to Write Persuasive Texts of Class VIII Students of SMP Negeri 9 East Jakarta - Ain, Hurul; Haryanti, Ade Siti; Ridhowati (Jurnal Profesi Pendidikan, 2025)
The purpose of this study is to find out how the use of audio-visual advertising media impacts the ability of grade VIII students to write persuasive essays at SMP Negeri 9 East Jakarta. This experimental study created a control group specifically for post-tests. The population is 288 students, and the number of samples used in the study is 60 students. We deliberately use sampling to obtain assessment sheets, which serve as experimental instruments. The results of the study showed that based on the results of the t-test with a tcal value = 14.96 > t table = 5.09, thus H0 was rejected, but H1 was accepted. Research at SMP Negeri 9 East Jakarta shows that the use of audio-visual advertising media has a considerable influence on the ability of Class VIII students to write persuasive essays. In terms of average learning outcomes, the experimental class using audiovisual advertising learning media received a score of 80.5.